Situation of Classroom Research Practices by Secondary Chemistry Teachers in Luang Prabang Municipality - ONSENGTAVANH , Fongmany; ANOLAC, vira; KHAMMELEESAYSUE, Her; DEELIVONG , Somphone; LADDAVONE, vilasack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research is quantitative research, which aims to study the status of classroom research practices by Secondary Chemistry Teachers in LuangPrabang Municipality, LuangPrabang Province. The target group for this research consisted of 68 participants, selected using a simple random sampling method. The tool used for collecting data on the classroom research practices of secondary chemistry teachers in Luang Prabang Municipality, Luang Prabang Province, the questions were following by 5-level Rating Scale. Data analysis utilized Descriptive Statistics to find the mean (Xˉ) and the standard deviation (S.D). The research findings showed that Study of Classroom Research Practices by Secondary Chemistry Teachers in Luang Prabang Municipality, Luang Prabang Province, was generally at a low level (Xˉ=2.16 and S.D.=0.37). Among the aspects studied, the highest mean score was found in promotion and support (Xˉ=2.27; S.D.=0.28), followed by In terms of teachers' ability to conduct research in the classroom (x = 2.25 S.D = 0.30), in terms of implementation of research in the classroom (overline x = 2.22 S.D = 0.36), utilization of classroom research results (Xˉ=2.18; S.D.=0.37), and guidance and monitoring of classroom research (Xˉ=2.14; S.D.=0.35). The aspect with the lowest mean score was dissemination of research results (Xˉ=1.91; S.D.=0.57).